Molecular Characterization of the Tumor Microenvironment in Renal Medullary Carcinoma - Tourigny, David S.; Zucker, Mark; Kim, Minsoo; Russo, Paul; Coleman, Jonathan; Lee, Chung-Han; Carlo, Maria I.; Chen, Ying-Bei; Hakimi, A. Ari; Kotecha, Ritesh R.; Reznik, Ed (Frontiers in Oncology, 2022)
Renal medullary carcinoma (RMC) is a highly aggressive disease associated with sickle hemoglobinopathies and universal loss of the tumor suppressor gene SMARCB1. RMC has a relatively low rate of incidence compared with other renal cell carcinomas (RCCs) that has hitherto made molecular profiling difficult. To probe this rare disease in detail we performed an in-depth characterization of the RMC tumor microenvironment using a combination of genomic, metabolic and single-cell RNA-sequencing experiments on tissue from a representative untreated RMC patient, complemented by retrospective analyses of archival tissue and existing published data. Our study of the tumor identifies a heterogenous population of malignant cell states originating from the thick ascending limb of the Loop of Henle within the renal medulla. Transformed RMC cells displayed the hallmarks of increased resistance to cell death by ferroptosis and proteotoxic stress driven by MYC-induced proliferative signals. Specifically, genomic characterization of RMC tumors provides substantiating evidence for the recently proposed dependence of SMARCB1-difficient cancers on proteostasis modulated by an intact CDKN2A-p53 pathway. We also provide evidence that increased cystine-mTORC-GPX4 signaling plays a role in protecting transformed RMC cells against ferroptosis. We further propose that RMC has an immune landscape comparable to that of untreated RCCs, including heterogenous expression of the immune ligand CD70 within a sub-population of tumor cells. The latter could provide an immune-modulatory role that serves as a viable candidate for therapeutic targeting.